'Dobra polska mowa': Monoglot ideology, multilingual reality and 'Polish' organisations in the UK - Kozminska, K; Zhu, H (De Gruyter, 2021)
This article examines the tension between multilingual reality of migrant life and monoglot standard ideology in Polish grassroots organisations in the UK. Drawing on linguistic ethnographic fieldwork from 2017 to 2019, we show that while flexible multilingual practices characterise the community’s multilingual reality, a preference for monolingual standard Polish exists in community activities and online profiles. We argue that, through common orientation to the denotational code and national identity, the organisations give preference to language rather than the speech community of the immediate surroundings and attempt to create a representation of a timeless unified Polish community in line with the static framework of the European nation-state that promotes linguistic, cultural and racial purity. While advocating sedentary, permanent and classed images of migration and integration into British society, the organisations marginalise uses of other language varieties and erase observed historical, class and regional differences within the community.